Substansi di Atas Formalitas: Analisis Pertimbangan Hakim Dalam Sengketa Penetapan Wajib Pajak Non-Efektif - Adiasih, Ning; Sihombing, Januardo Sulung Partogi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Determining non-effective taxpayer status in Indonesia often generates legal disputes due to administrative formalities versus substantial requirements conflicts. This study examines judicial considerations in tax court decisions regarding ineffective taxpayer determination disputes, specifically analyzing the case between Mrs. Sri Roosmini and the Primary Tax Office of Kebayoran Lama, South Jakarta. This research employs a normative juridical approach, analyzing Tax Court Decision No. 009544.99/2020/PP/M—IB from 2020 and the Supreme Court Decision Reg. No. 4910/B/PK/Pjk/2022 from 2022. The study examines legal documents, statutory regulations, and judicial reasoning to understand the substance-over-form principle application in tax law. The Tax Court granted the taxpayer's appeal entirely, canceling the business turnover correction of Rp270,659,270.00. The Supreme Court subsequently rejected the Directorate General of Taxes' judicial review application, affirming that Mrs. Roosmini had fulfilled the substantive requirements for non-effective taxpayer status despite administrative deficiencies claimed by the tax office. The decisions emphasize the importance of substance over formalities in ineffective taxpayer determination, establishing that administrative requirements should not override substantial compliance with legal criteria. This precedent strengthens legal certainty and taxpayer protection in Indonesia's tax administration system.